PROGRAM SERVICE RECOVERY UNTUK PENCIPTAAN KEPUASAN PELANGGAN DI ANGKUTAN KERETA API DAERAH OPERASI 2 BANDUNG - Lestari, Fitri (Universitas Pendidikan Indonesia, 2016)
The development modes of transportation in Indonesia led to competition in the various modes such as by land; sea and air were increasing. Railway is one mode of transportation, especially as the most dominated by the passenger in Bandung. Due to higher competition pattern, efforts were made to improve passenger satisfaction. Various complaints can occur, and will increase if not addressed promptly so that the company should seek to restore service (service recovery) that passengers are satisfied. This study was conducted to determine how the implementation of the program service recovery Argo Gede Train, perceived satisfaction of passengers and how much influence the program service recovery on customer satisfaction.The object of this research was Argo Gede Train passenger route Bandung-Jakarta. The independent variable in this study was a service recovery program (X), and the dependent variable was customer satisfaction (Y). The type of research was descriptive verification, through explanatory survey method with simple random sampling technique, and 100 respondents were analyzed by linear regression analysis. The data used in this study are primary data and secondary data, with data collection through interviews, direct observations, and questionnaires' research, and literature studies. The results showed in the service recovery program, has improved the accuracy of the biggest scores. The results showed that the service recovery program has the effect of 47.80% on customer satisfaction to note that the service recovery program has a significant impact on customer satisfaction. Keywords: Service Recovery, Customer Satisfaction